A self-organizing approach: Time synchronization for the HeNodeBs in heterogeneous network - Hasan M.K.; Ismail A.F.; Abdalla A.H.; Ramli H.A.M.; Hashim W.; Razzaque A.; Khairolanuar M.H. (Springer Verlag, 2023)
Femtocell; Heterogeneous networks; Internet; Internet protocols; Mobile telecommunication systems; Standards; Synchronization; HeNodeB; Heterogeneous Network (HetNet); IEEE 1588; Linear regression algorithms; LTE/LTE-Advanced; Message transmissions; Self-organizing approaches; Self-organizing method; Wireless telecommunication systems